Multimode Representation of the Magnetic Field for the Analysis of the Nonlinear Behavior of Solar Activity as a Driver of Space Weather - Elena Popova; Anatoli I. Popov; Roald Sagdeev (Mathematics, 2022)
Estimating and predicting space weather is important to the space industry and space missions. The driver of space weather, especially near the Earth, is solar activity, the study of which is an important task. In particular, there is a direction of problems based on models of solar magnetic field generation that require research. In our work, we build a nonlinear dynamic system of equations that describes the behavior of the solar magnetic field harmonics based on the alpha-omega dynamo model. We found that, at the beginning of the magnetic field generation process, when the dynamo number significantly exceeds the threshold, the most rapidly growing waves are in the lead. Then, over time, these waves stop growing quite quickly. In this case, the initially slowly increasing harmonics of the magnetic field become the leaders, which then make the main contribution to the process of magnetic field generation.